2017
DOI: 10.1021/acs.jpca.7b05099
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Divergent Thermal Conductivity in Single Polythiophene Chains Using Green–Kubo Modal Analysis and Sonification

Abstract: Abstract:We used molecular dynamics simulations, the Green-Kubo Modal Analysis (GKMA) method and sonification to study the modal contributions to thermal conductivity in individual polythiophene chains. The simulations suggest that it is possible to achieve divergent thermal conductivity and the GKMA method allowed for exact pinpointing of the modes responsible for the anomalous behavior. The analysis showed that transverse vibrations in the plane of the aromatic rings at low frequencies ~ 0.05 THz are primari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 64 publications
(156 reference statements)
4
14
0
Order By: Relevance
“…Depending on the assigned initial velocities, we observed that the Green-Kubo integral differently evolved in time: therefore, for some trajectories (actually 6 out of 10) the Green-Kubo integral was eventually found to reach a constant value, while for the remaining ones we observe an overall divergence. The diverging behavior and its chaotic dependence on the initial conditions was previously observed in different single polymer chains [12][13][14]. A similar behavior has been also observed in 2D graphene subjected to a uniaxial strain [35].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Depending on the assigned initial velocities, we observed that the Green-Kubo integral differently evolved in time: therefore, for some trajectories (actually 6 out of 10) the Green-Kubo integral was eventually found to reach a constant value, while for the remaining ones we observe an overall divergence. The diverging behavior and its chaotic dependence on the initial conditions was previously observed in different single polymer chains [12][13][14]. A similar behavior has been also observed in 2D graphene subjected to a uniaxial strain [35].…”
Section: Resultssupporting
confidence: 80%
“…In particular, the nonintensive character of κ has been experimentally observed in 1D-like carbon and boron-nitride nanotubes [3,4] as well as in SiGe nanowires [5], while a similarly characterized anomalous heat conduction has been theoretically shown to occur in 1D Fermi-Pasta-Ulam [6] and diatomic Toda lattices [7]. Atomistic simulations as well predict anomalous heat conduction in different 1D-like materials, such as carbon nanotubes [8,9], silicon nanowires [10], and polymer chains [11][12][13][14].…”
Section: Introductionmentioning
confidence: 92%
“…Besides, Lv and Henry derived a new method, Green–Kubo modal analysis (GKMA), which combines the lattice dynamics with the Green–Kubo formula for the direct calculation of the thermal conductivity contributions from different types of modes. Using GKMA method, Lv et al observed the divergent thermal conductivity in a single PT chain. The anomalous heat conduction phenomenon originates from the transverse vibrations in the plane of the aromatic rings at low frequencies around 0.05 THz, which can be determined by the sonification of the modal heat flux.…”
Section: Theoretical and Experimental Approachesmentioning
confidence: 99%
“…In recent years, thermal conductivity of conductive polymers has been investigated by both experimental and theoretical studies . Table 1 lists the thermal conductivity value for some typical conductive polymers, which are two to three orders of magnitude lower than that of conventional semiconducting crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation